Epidermal morphology of the genus dialium (fabaceae: caesalpinioideae) (1997)
Epidermal morphology of adaxial and abaxial leaflet surfaces of the five species in the genus Dialium (Fabaceae : Caesalpinoideae) were studied by light microscopy. The epidermises are composed of cells which are isodiametric, irregular or both types in outline. Anticlinal walls are either straight, curved or undulate. Leaflets of all taxa are hypostomatic. Paracytic stomata occur in all species except D. guineense that posses both paracytic and staurocytic stomata. Other features of the epidermis that show variation include stomatal size and density, size and density of epidermal cells, and type, size, shape, frequency and basal cells of the trichomes. An indented, dichotomous key for identifying the species is presented.